Metformin Improves Glycemic Control and Postprandial Metabolism and Enhances Postprandial Glucagon-Like Peptide 1 Secretion in Patients With Type 2 Diabetes and Heart Failure: A Randomized, Double-Blind, Placebo-Controlled Trial - Melenovský, Vojtěch; Hošková, Eva; Velebová, Kateřina; Veleba, Jiří; Borlaug, Barry A; Benes, Jan; Kuda, Ondřej; Čajka, Tomáš; Segeťová, Markéta; Thieme, Lenka; Kopecký, Jan; Kopecký, Jan; et al. (Clinical diabetes, 2025)
This randomized trial tested the effect of metformin on glycemic control and cardiac function in patients with heart failure (HF) and type 2 diabetes while evaluating intestinal effects on selected gut microbiome products reflected by trimethylamine-N-oxide (TMAO) and gut-derived incretins. Metformin treatment improved glycemic control and postprandial metabolism and enhanced postprandial glucagon-like peptide 1 (GLP-1) secretion but did not influence cardiac function or the TMAO levels. Metabolic effects of metformin in HF may be mediated by an improvement in intestinal endocrine function and enhanced secretion of the gut-derived incretin GLP-1.